(3MLjI GdTgQI hLhGR GdGYJeGO YdjgG aj GKHGJ GdCMcGes - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs
(3ChdgG (B:s
(3GdMeO ddg (B...(3bO Mci TjNfG GdTgjO aj GdPcQi MSf HYV GdCUMGH GdMGb GdTgQI HGdELeGY hSjbQ Hg Ef cGf GdeQGO GdMGbgG aj GdMLjI dG aj chfgG ELeGYG bGd dCf YOGdJge JefY (B...s
(3BNQgG (B:s
... (3Pdc GdeTJQc HUjQhQI Mce GdTQY HGdfSHI dCaYGdfG GfJgi cdGeg hajg JCjjO deG PcQfG hJbhjI deG SWQfG hEf cGf aj ehGVY ajeG PcQg GTJHGgGJ djS dgPg GdQSGdI eMd fTQgG JeJs
(3Vef eLehY JdjgG QSGdI aj JMbjb GdbjGS ddeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 17s
(3GdPQjYI (B6\1479s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs